Pengaruh Pupuk Organik (Kandang Kambing) Terhadap Pertumbuhan dan Hasil Tanaman Tomat (Lycopersicum Esculentum Mill) - Agus Burhan (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to determine the effect of giving organic fertilizer (goat cage) with different doses on the growth and yield of tomato plants. The study used a randomized block design with one factor, namely P0 = No treatment (control), P1 = dose of goat manure 4 kg.plot-1 equivalent to 10 t.ha-1, P2 = dose of goat manure 6 kg.plot-1 equivalent with 15 t.ha-1, P3 = dose of goat manure 8 kg.plot-1 is equivalent to 20 t.ha-1, P4 = dose of goat manure 10 kg.plot-1 is equivalent to 25 t.ha-1. The results showed that the treatment with various doses of organic fertilizer (goat cage) was 6 kg. gave results that had a very significant effect on the observation variable stem diameter 45 DAP, tomato plants showed an average of 3.79 cm, had a very significant effect on fruit weight of tomato plants on the observation variable showed an average of 232.50, had a very significant effect on the observed variables. flowering age of tomato plants with an average of 30, and significantly affected the observed variables of tomato plant height 45 DAP, number of leaves 15 DAP and 30 DAP and stem diameter 15 DAP